A Central Amygdala–Ventrolateral Periaqueductal Gray Matter Pathway for Pain in a Mouse Model of Depression-like Behavior. (May 2020) - Yin, Weiwei; Mei, Lisheng; Sun, Tingting; Wang, Yuping; Li, Jie; Chen, Changmao; Farzinpour, Zahra; Mao, Yu; Tao, Wenjuan; Li, Juan; Xie, Wen; Zhang, Zhi
Abstract : Background: The mechanisms underlying depression-associated pain remain poorly understood. Using a mouse model of depression, the authors hypothesized that the central amygdala–periaqueductal gray circuitry is involved in pathologic nociception associated with depressive states. Methods: The authors used chronic restraint stress to create a mouse model of nociception with depressive-like behaviors. They then used retrograde tracing strategies to dissect the pathway from the central nucleus of the amygdala to the ventrolateral periaqueductal gray. The authors performed optogenetic and chemogenetic experiments to manipulate the activity of this pathway to explore its roles for nociception. Results: The authors found that γ-aminobutyric acid–mediated (GABAergic) neurons from the central amygdala project onto GABAergic neurons of the ventrolateral periaqueductal gray, which, in turn, locally innervate their adjacent glutamatergic neurons. After chronic restraint stress, male mice displayed reliable nociception (control, mean ± SD: 0.34 ± 0.11 g, n = 7 mice; chronic restraint stress, 0.18 ± 0.11 g, n = 9 mice, P = 0.011). Comparable nociception phenotypes were observed in female mice. After chronic restraint stress, increased circuit activity was generated by disinhibition of glutamatergic neurons of the ventrolateral periaqueductal gray by local GABAergic interneurons via receiving enhanced central amygdala GABAergic inputs. Inhibition of this circuit increased nociception in chronic restraint stress mice (median [25th, 75th percentiles]: 0.16 [0.16, 0.16] g to 0.07 [0.04, 0.16] g, n = 7 mice per group, P < 0.001). In contrast, activation of this pathway reduced nociception (mean ± SD: 0.16 ± 0.08 g to 0.34 ± 0.13 g, n = 7 mice per group, P < 0.001). Conclusions: These findings indicate that the central amygdala–ventrolateral periaqueductal gray pathway may mediate some aspects of pain symptoms under depression conditions. Abstract : Chemogenetic experiments in a mouse model of depression reveal the involvement of a neural circuitry between the central amygdala and the periaqueductal gray in nociception. In this mouse model, pathologically increased activity of inhibitory γ-aminobutyric acid–mediated neurons in the central amygdala will result in the inhibition of inhibitory γ-aminobutyric acid–mediated neurons in the periaqueductal gray. This, in turn, will lead to the activation of glutamatergic cells involved in periaqueductal gray-mediated nociception. These findings provide a framework for how the central amygdala–periaqueductal gray circuitry may play a role in coping with nociception in depressive states.Supplemental Digital Content is available in the text.